Penerapan prinsip desain arsitektur biofilik pada Riau Mitigation and Disaster Management Center - Miftahul Karima; Yohannes Firzal; Gun Faisal (ARTEKS : Jurnal Teknik Arsitektur, 2020)
The application of biophilic architecture design principle on Riau Mitigation and Disaster Management Center Disaster is a series of events that cause significant loss, even casualties. Indonesia, which was called as Laboratory of Disaster was characterized by the increase of complexity and number of disasters each year, which make mitigation and disaster management skill should be a top priority. Hence, a facility where education for mitigation could be held as needed. This facility was designed for education, recreation, and last evacuation shelter, located in Pekanbaru, Riau, due there wasn’t this type of facility in the province. Considering its function, biophilic design was chosen due to its principle of respecting nature; hence users’ productivity, physical and mental health increase and the existence of natural elements could give comfort and refuge. The design methodology was a site survey and data collection about Biophilic architecture design principles and mitigation and disaster prevention center from journals. The result of this methodology is a design of Mitigation and Disaster Management Center in Riau. © 2020 Miftahul Karima, Yohannes Firzal, Gun Faisal